Ultrasonic distance detector - 454353 Adibah Adeeb (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Control & Instrumentations)) - Universiti Teknologi Malaysia, 2001